2014
DOI: 10.4196/kjpp.2014.18.1.41
|View full text |Cite
|
Sign up to set email alerts
|

The Modulatory Role of Spinally Located Histamine Receptors in the Regulation of the Blood Glucose Level in D-Glucose-Fed Mice

Abstract: The possible roles of spinal histamine receptors in the regulation of the blood glucose level were studied in ICR mice. Mice were intrathecally (i.t.) treated with histamine 1 (H1) receptor agonist (2-pyridylethylamine) or antagonist (cetirizine), histamine 2 (H2) receptor agonist (dimaprit) or antagonist (ranitidine), histamine 3 (H3) receptor agonist (α-methylhistamine) or antagonist (carcinine) and histamine 4 (H4) receptor agonist (VUF 8430) or antagonist (JNJ 7777120), and the blood glucose level was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…In our previous study, we already demonstrated the role of spinally located histamine receptor in regulation of the blood glucose level in D-glucose fed mice model (Sim et al 2014). In the present study, we found that i.t.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In our previous study, we already demonstrated the role of spinally located histamine receptor in regulation of the blood glucose level in D-glucose fed mice model (Sim et al 2014). In the present study, we found that i.t.…”
Section: Discussionsupporting
confidence: 71%
“…In our previous study, we reported that the spinally located histamine H2 receptor activation and histamine receptors H1 or H3 blockade play a modulatory role in blood glucose regulation in D-glucose fed mice model (Sim et al 2014). In the present study, we found that the elevation of the blood glucose level induced by IMO was attenuated by i.c.v.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The blood glucose level is regulated not only by insulin but also by the histamine system [37,38]. Our study showed a decrease in the plasma histamine level of chickens receiving Cr at 3 mg/kg, irrespective of the form used.…”
Section: Discussionmentioning
confidence: 52%
“…It is likely that Cr, by increasing the plasma insulin level, causes a decrease in the concentration of histidine, which is a precursor of histamine. In addition to the direct involvement of histamine receptors in the regulation of blood glucose, several studies have shown that the activation or deactivation of histamine receptors appears to have a modulating role in the regulation of the blood glucose level [38].…”
Section: Discussionmentioning
confidence: 99%